Engineering expansion : the U.S. Army and economic development, 1787-1860 - Adler, William D. (American governance., 2021)
"This book details the host of ways in which the U.S. Army impacted economic development in the period from the writing of the Constitution to the eve of the Civil War, and has analyzed the political forces behind the Army's actions. The Army's promotion of science and technology, its assistance in building infrastructure across the nation, its opening of new regions for white settlement through wars against native tribes and foreign nations, and its unifying of the nation by enforcing central state policies all propelled economic growth and helped launch the United States into a new era of commercial and industrial expansion at the end of the nineteenth century. Despite its small size, the Army was an actor of immense significance to the development of the American economy, as well as to the development of central state capacity"--